Kontekstualisasi Moderasi Beragama melalui Komunikasi Antarbudaya: Studi Kasus Komunitas Muslim Papua di Sorong, Indonesia - Hidayat, Rahmat; Andriyan, Yoga; Susim, Rosalita; Inai, Abdur Rahman; Sohnui, Suhailee (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2025)
Religious moderation is often portrayed as a normative or policy-driven concept; nevertheless, its actual implementation in minority Muslim situations, particularly in culturally complex regions such as Papua, is inadequately explored. This study aims to examine the expression, negotiation, and maintenance of religious moderation via intercultural communication among Muslim Papuans in Sorong, Indonesia, a multicultural frontier marked by substantial interethnic and interreligious interactions. A qualitative case study methodology was employed to collect data through in-depth interviews, participatory observation, and document analysis, involving community leaders, religious figures, and local residents. The findings demonstrate that religious moderation operates as both a theoretical construct and a communicative practice embedded in daily interactions, involving the utilisation of hybrid languages, participation in communal social activities, and the negotiation of religious identity across varied contexts. This study theoretically enhances intercultural communication frameworks by demonstrating that in minority contexts, religious moderation functions as a relational and adaptive communication strategy rather than a fixed theological position. The results suggest that efforts to promote religious harmony must go beyond authoritative narratives and incorporate locally established communication practices and cultural standards. This study offers new perspectives by conceptualising Islamic moderation as a lived and communicatively constructed phenomenon within a Global South framework, offering a nuanced understanding of the practice and negotiation of Islam across diverse socio-cultural environments.